The effect of demographic and disease variables on Schneiderian membrane thickness and appearance - Yildirim, Tuba Talo; Guncu, Guliz Nigar; Goksuluk, Dincer; Tozum, Melek Didem; Colak, Mehmet; Tozum, Tolga Fikret (Elsevier Science Inc, 2017)
Objectives. The purpose of this study was to evaluate the prevalence of sinus mucosal thickening (MT) and mucosal appearance (MA) in a patient population as detected with cone beam computed tomography (CBCT) and to determine the effects of various disease and demographic factors on MT and MA. Study Design. The retrospective study consisted of CBCT images of 1000 maxillary arches in 500 patients. The arches were divided into 3 groups (atrophic, partially atrophic, and nonatrophic) according to the type of the maxillary dental crest. The CBCT scans were assessed to detect the prevalence of maxillary sinus MT and MA. chi(2) analysis was used to determine the significance of association of periodontal bone loss (PBL), periapical (PA) status, alveolar crest type, age, and gender on sinus MT and MA. Results. MT was significantly associated with PBL (P = .004), PA status (P = .001), and gender (P < .01). MA was significantly associated with PBL (P = .038), PA status (P = .009), and gender (P < .020). There were no significant associations between age or crest type and either MT or MA. Conclusions. Periodontal bone loss, PA lesions, and gender may have an association with MT of the maxillary sinus.
Keywords: Sinus Floor Elevation; Beam Computed-Tomography; Maxillary Sinus; Posterior Maxilla; Implant Survival; Ostium Patency; Risk-Factors; Bone Loss; Augmentation; Perforation